Experimental Determination of the Impact of Floats on the Aerodynamic Characteristics of an OSA Model in Symmetric Flow - Michał FRANT; Stanisław WRZESIEŃ; Maciej MAJCHER (Problemy Mechatroniki)
This paper presents the results of experimental determination of the impact of floats on the aerodynamic characteristics of an OSA model in symmetric flow. The studies have been performed in the low-speed wind tunnel at the Military University of Technology (MUT, Warsaw, Poland). The aircraft model was examined at the dynamic pressure q = 500 Pa in the following angle of attack range alfa= -28 to+28 deg. The investigations have been performed for an aircraft model under plain configuration with floats and without floats. The influence of elevator and flap inclination on the aerodynamic characteristics of the model has also been analysed. The obtained values of aerodynamic drag coefficient, lift coefficient, pitching moment coefficient and lift-to-drag ratio have been presented in the form of tables and graphs. The studies performed demonstrated that the use of floats causes the increase of aerodynamic drag coefficient CD, maximum lift coefficient CLmax as well as critical angle of attack alfa cr. The decrease of lift-to-drag ratio has also been observed. Its value in the case of the model with floats was up to 20% lower than in the model without floats. The studies also showed that the model equipped with floats had a lower longitudinal static stability margin than the model without floats.